Keabsahan Hukum Talak di Bawah Tangan (Analisis Perspektif Tengku Dayah di Kabupatan Aceh Besar, Aceh, Indonesia) - Abrar Zym (Ar-Raniry: International Journal of Islamic Studies, 2020)
One of the reasons for the end of the marriage was the declaration of divorce that was carried out in court (The Court of Syar'iyah). However, sometimes there is also the practice of divorce outside the court through the religionist (or known by teungku) or village officials, as happened in Aceh Besar district. The purpose of this study was to determine the causes of divorce outside the court that occurred in Aceh Besar District and how the tengku perspective provides an understanding of the problem of under-handed divorce, especially in society. The type of research in this is qualitative with a normative legal research approach. The cause of divorce outside the court in Aceh Besar District is a habit, lack of legal awareness, personal problems that must be covered up, previous marriages through illegal qadhi, economic factors and the long trial process. The perspective of teungku in providing an understanding of the issue of divorce outside the court is legal.